INTERNAL CONTROL SYSTEM: SOX-REQUIREMENTS APPROACH TO ASSESSMENT - K. O. Nazarova; O. O. Zaremba; T. Yu. Kopotiienko; V. O. Mysiuk (Фінансово-кредитна діяльність: проблеми теорії та практики, 2018)
The European integrational vector of Ukraine's development significantly enhances the requirements for the quality of enterprises` financial reporting that are subjects of public interest, and obliges them to build an effective system of internal control due to the open economy conditions and business chalanges, the availability of a reliable information environment, which would create unquestionable guarantees of investment preservation, becomes significant for the owners of invested capital. By adapting the best practice of doing business, domestic business entities seek to improve the reliability of their internal control system through the usage of tools that have been tested by many years successful business in developed countries. Particularly, under these conditions, the provisions of the Sarbanes-Oxley Act, whose previous perception was focused directly on compliance with the law, deserve merit, and participation in risk management was merely an idea. Today, compliance with the law is an important part of the company's risk management system. In the conditions of doing business in an open economy, this objective can only be achieved if the reliable control environments of the company represented by its internal control system are set up. Domestic methods for assessing internal control systems do not take into account the enterprises` needs to undergo SOX control and sjould be improved. The concept of constructing a matrix of internal control system assessment, which includes Control Matrix, Assessment, Remediation and Testing, is developed. The said units of the matrix of the internal control system assessment cover the homogeneous nature of the group of business processes depending on the factors that may affect the enterprise control environment. Each of these blocks can be expanded, depending on the size of the enterprise. The proposed development allows organizing the qualitative and operational work of the internal control system, which will contribute to the effectiveness of making managerial decisions and aimed at preventing the occurrence of fraud.